Phytotoxic Activity of Ocimum tenuiflorum Extracts on Germination and Seedling Growth of Different Plant Species - A. K. M. Mominul Islam; Hisashi Kato-Noguchi (The Scientific World Journal)
Phytotoxic activity of Ocimum tenuiflorum (Lamiaceae) plant extracts was investigated against the germination and seedling growth of cress (Lepidium sativum), lettuce (Lactuca sativa), alfalfa (Medicago sativa), Italian ryegrass (Lolium multiflorum), barnyard grass (Echinochloa crus-galli), and timothy (Phleum pratense) at four different concentrations. The plant extracts at concentrations greater than 30 mg dry weight equivalent extract mL−1 reduced significantly the total germination percent (GP), germination index (GI), germination energy (GE), speed of emergence (SE), seedling vigour index (SVI), and coefficient of the rate of germination (CRG) of all test species except barnyard grass and GP of lettuce. In contrast, time required for 50% germination (T50) and mean germination time (MGT) were increased at the same or higher than this concentration. The increasing trend of T50 and MGT and the decreasing trend of other indices indicated a significant inhibition or delay of germination of the test species by O. tenuiflorum plant extracts and vice versa. In addition, the shoot and root growth of all test species were significantly inhibited by the extracts at concentrations greater than 10 mg dry weight equivalent extract mL−1. The I50 values for shoot and root growth were ranged from 26 to 104 mg dry weight equivalent extract mL−1. Seedling growth was more sensitive to the extracts compared to seed germination. Results of this study suggest that O. tenuiflorum plant extracts have phytotoxic properties and thus contain phytotoxic substances. Isolation and characterization of those substances from this plant may act as a tool for new natural, biodegradable herbicide development to control weeds.